A Sand County almanac & other writings on ecology and conservation - Leopold, Aldo, 1886-1948 (Library of America, 2013)
A Sand County almanac is often hailed as a foundational work of the modern environmental movement. Here, it is paired with over fifty other pieces by Leopold: uncollected articles, essays, speeches, and other writings that chart the evolution of his ideas over the course of three decades.